LAW AS A TOOL OF SOCIAL CONTROL IN THE CASE OF THUG RATION - Tomy Ahmad Bustomi; Catharina Dewi Wulansari (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Discussion of law as a means of social control is related to methods and disciplines in sociology. The use of various disciplines against law is very important when we discuss it as a tool of social control. One of the crucial points in this topic is the need for law to meet the real needs of society, so that the law can function properly. Another important aspect is the supremacy of the application of the law or the rule of law itself. The rule of law is needed to realize the function of law as a tool of social control by fully considering the sociological aspects of law enforcement. In this case, the author wants to try to study the sociology of law as a social control over the political phenomenon of crime. It is undeniable that it often happens in Indonesia as CSOs have penetrated the business world and of course with the franchise system, with deals that have been agreed in such a way, CSOs have evolved into fields.